Pengaruh Model Pembelajaran MURDER (Mood, Understand, Recall, Digest, Expand, Review) terhadap Hasil Belajar Matematika Siswa - Dedy Setyawan; Ernawati; Husnul Khatima (EQUALS: Jurnal Ilmiah Pendidikan Matematika, 2026)
This study employed a quasi-experimental research design to examine the effect of the MURDER learning model on the mathematics learning outcomes of Grade X students at SMA DDI Maros. The population of this study consisted of all Grade X students at SMA DDI Maros. The sample was selected using a random class sampling technique, resulting in two classes: an experimental class and a control class. The research instruments consisted of a validated multiple-choice mathematics achievement test and an observation sheet used to measure the implementation of the learning model. The data were analyzed using descriptive and inferential statistical techniques. The results indicated that the average mathematics learning outcomes of students in the experimental class were higher than those of students in the control class. The average posttest score of the experimental class was 84.03, with a standard deviation of 3.54, while the average posttest score of the control class was 69.40, with a standard deviation of 1.96. Based on the results of the t-test, the calculated t-value was greater than the critical t-table value, and the significance value was lower than the 0.05 significance level. Therefore, the null hypothesis was rejected. Furthermore, the average percentage of learning implementation reached 89.84%, which was categorized as very good. These findings indicate that the MURDER learning model can be implemented consistently and effectively in the mathematics learning process.